Using Canva and Microsoft Teams to support students’ writing tasks - Zahidah Wan Sulaiman, Wan; ali, zuraina; Mohd Ali, Zarina; Hussain Shahid, Shahid; Ishtiaq, Muhammad; Abu Bakar, Norsuhaily (Institute of Advanced Engineering and Science, 2025)
Teachers and students face difficulties in remote learning. These difficulties can be greatly reduced by utilizing applications, such as Microsoft Teams (MS Teams) and Canva. This study investigates the effectiveness of using Canva and MS Teams as helpful resources for students assigned to write informative speech essays. Employing a sequential explanatory research design in a mixed-method approach, the study involved sixteen English majors from a private university located on Malaysia’s East Coast. Students used MS Teams to complete pre-and post-tests, and afterward, interviews were held to learn more about how they felt about using Canva. The pre and post-tests showed that students improved their writing abilities when using MS Teams since they had a chance to collaborate with their peers and teachers. Qualitative findings also revealed that online learning environments promoted interaction between students and teachers and between students and their peers. The results suggest that incorporating web tools like MS Teams and Canva could enhance students’ learning experience as they complete their writing projects. Overall, this study highlights the potential benefits of incorporating web technologies into the writing process and underscores the importance of seeking student feedback to improve the effectiveness of these tools.